Effects of inhaled JAK inhibitor GDC-4379 on exhaled nitric oxide and peripheral biomarkers of inflammation. (August 2022) - Chen, Hubert; Kunder, Rebecca; Zou, Yixuan; Staton, Tracy; Zhu, Rui; Galanter, Joshua; Gugelmann, Hallam; Owen, Ryan; Grimbaldeston, Michele A.; Chang, Joanna K.; Durk, Matthew R.; Eliahu, Avi; et al.
Abstract: Background: Janus Kinases (JAKs) mediate activity of many asthma-relevant cytokines. GDC-0214, an inhaled small molecule JAK1 inhibitor, has previously been shown to reduce fractional exhaled nitric oxide (FeNO) in patients with mild asthma, but required an excessive number of inhalations. Aim: To assess whether GDC-4379, a new inhaled JAK inhibitor, reduces FeNO and peripheral biomarkers of inflammation. Methods: This study assessed the activity of GDC-4379 in a double-blind, randomized, placebo-controlled, Phase 1 study in patients with mild asthma. Participants included adults (18–65y) with a diagnosis of asthma for ≥6 months, forced expiratory volume in 1 s (FEV1 )> 70% predicted, FeNO >40 ppb, using as-needed short-acting beta-agonist medication only. Four sequential, 14-day, ascending-dose cohorts (10 mg QD, 30 mg QD, 40 mg BID, and 80 mg QD) of 12 participants each were randomized 2:1 to GDC-4379 or placebo. The primary activity outcome was percent change from baseline (CFB) in FeNO to Day 14 compared to the pooled placebo group. Safety, tolerability, pharmacokinetics, and pharmacodynamic biomarkers, including blood eosinophils, serum CCL17, and serum CCL18, were also assessed. Results: Of 48 enrolled participants, the mean age was 25 years and 54% were female. Median (range) FeNO at baseline was 79 (41–222) ppb. GDC-4379 treatment led to dose-dependent reductions in FeNO. Compared to placebo, mean (95% CI) percent CFB in FeNO to Day 14 was: −6 (−43, 32) at 10 mg QD, −26 (−53, 2) at 30 mg QD, −55 (−78, −32) at 40 mg BID and −52 (−72, −32) at 80 mg QD. Dose-dependent reductions in blood eosinophils and serum CCL17 were also observed. Higher plasma drug concentrations corresponded with greater FeNO reductions. No serious AEs occurred. The majority of AEs were mild to moderate. The most common AEs were headache and oropharyngeal pain. Minor changes in neutrophils were noted at 80 mg QD, but were not considered clinically meaningful. Conclusions: In patients with mild asthma, 14-day treatment with GDC-4379 reduced FeNO levels and peripheral biomarkers of inflammation. Treatment was well tolerated without any major safety concerns. Australian New Zealand Clinical Trials Registry: ACTRN12619000227190. Highlights: JAKs mediate the activity of asthma-relevant cytokines IL-4, IL-5, IL-13, and TSLP. GDC-4379 is a JAK inhibitor that can be administered using a dry powder inhaler. GDC-4379 caused dose-dependent reductions in FeNO, a biomarker of airway inflammation. GDC-4379 was generally safe and well-tolerated, and did not raise any significant safety concerns.